Assessing the Impact of Reference Assistance and Library Instruction on Retention and Grades Using Student Tracking Technology - Krieb, Dennis (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2018)
Objective – To assess the impact of community college academic librarians upon student retention and grades through reference desk visits and attendance in library instruction classes.Methods – Student ID data used for this research was collected from students that visited the reference desk to consult about a course-related question or attended a library instruction class for a specific course. After consenting to share their student ID number, the students’ IDs were scanned and uploaded to a Blackboard Analytics data warehouse. A Pyramid Analytics reporting tool was used to query and extract student-level retention and grade data based upon whether the student had visited the reference desk or attended a library instruction class. Chi-square and Fisher’s exact tests were used to discern any statistical difference in retention rates and grades between students that engaged a librarian through reference or instruction and the general student population.Results – When comparing fall-to-fall retention for all degree-seeking students, students that visited the reference desk or attended a library instruction class had a statistically higher rate of retention. When comparing fall-to-fall retention within low-retention student cohorts, students that visited the reference desk or attended a library instruction class had higher rates of retention among all low-retention cohorts. Eight of 10 cohorts were statistically higher for library instruction and 6 of 10 cohorts were statistically higher for reference visits. With respect to course grades, only 1 of 5 high enrollment courses showed a higher grade average for students that attended a library instruction class. None of the differences in average grades between students that attended a library instruction class and all students in the five courses were statistically significant. For the impact of a reference visit upon a course grade, all five courses showed a higher average grade average for students that visited the reference desk for a question related to their course than all students in the course. Four of the 5 differences were statistically significant.Conclusions – The data collected by systematically tracking students that interact with community college librarians suggests that reference desk visits and attendance of library instruction classes both have a positive, statistically significant impact upon student retention. When looking at course grades, the data does not indicate a statistically significant positive or negative impact for library instruction. The impact of visiting the reference desk upon course grades does suggest a strong, statistically significant positive correlation.